Lobbying and the international fight against tax havens - Tobias Hauck (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2018)
Despite a variety of measures taken by high tax countries, the international fight against tax havens so far remained rather ineffective. This paper introduces lobbying as a possible explanation for this observation. I analyze the international fight against tax havens in a two country model in which the onshore country exerts pressure on domestic profit shifting firms and the low tax country lobbies against this measure. In this framework, I find that pressure and lobbying are strategic substitutes and that there is an extensive margin incentive for offshore lobbying. I also show that an increase in international integration leads to a decrease in the level of profit shifting, when starting out at high levels of international frictions. Finally, when allowing for a second low tax jurisdiction, the overall level of lobbying increases, but less than proportionally, as free-riding occurs.
urn:nbn:de:bvb:19-epub-43213-8
Keywords: H25; H26; F23; 330; International Taxation; Tax Avoidance; Pressure Policies; Tax Havens; International Lobbying